Expression of Escherichia coli araE and modified lacY genes in Campylobacter jejuni is not sufficient for arabinose transport. Issue 5 (16th July 2019) - Ramesh, Amritha; Ikeda, Naomi; Rubinchik, Sona; Karlyshev, Andrey V.
Abstract : Introduction. Unlike Escherichia coli, Campylobacter jejuni is unable to import a range of sugars, including arabinose, which makes common expression vectors, such as pBAD33, non-functional in these bacteria. Aim. The aim of this study was to investigate whether the E. coli transporters AraE and modified LacY (LacYA177C) would enable C. jejuni to uptake arabinose. Methodology and Results. The respective genes of E. coli were constitutively expressed in C. jejuni strain 11168H after integration into the chromosome via homologous recombination. Vectors carrying these genes also contained a reporter gene, gfp, under the control of the arabinose-inducible promoter, pBAD. These constructs were verified in E. coli by demonstrating the induction of gfp in the presence of arabinose. Integration of the genes into one of the rRNA gene clusters was verified by PCR and genome sequencing. The latter also confirmed that the inserted gene clusters contained no mutations. Expression of the gfp gene in the presence of arabinose inducer was monitored using fluorescence microscopy of colonies and fluorimetry using both whole cells and lysates. Conclusion. The results demonstrated the inability of C. jejuni to use arabinose transporters, which are fully functional in E. coli, suggesting a remarkable difference in the physiology of these bacteria.